Mind the gap: inheritance and inequality in retirement wealth - Lukas Brenner; Oscar A. Stolper (Intergenerational Justice Review)
Drawing on detailed German panel data, we find that gifts and inheritances substantially increase households’ private pension savings in accounts which are costly or impossible to withdraw prematurely. Back-of-the-envelope calculations suggest that (a) the average difference in bequest-induced private pension savings between heirs and non-heirs accrues to more than 40,000 euros at retirement, and that (b) it would take an average non-heir household roughly 14 years to match this gap. The sizable difference in private pension savings between heirs and non-heirs persists when we take into account other investments of heirs and non-heirs potentially intended to provide for old age. Our evidence supports the impact of gifts and inheritances on inequality in retirement wealth highlighted in recent research on intergenerational justice. We discuss several policy implications of our results.